2012
DOI: 10.1016/j.ijrobp.2010.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Adhere to Protocol Specified Radiation Therapy Guidelines Was Associated With Decreased Survival in RTOG 9704—A Phase III Trial of Adjuvant Chemotherapy and Chemoradiotherapy for Patients With Resected Adenocarcinoma of the Pancreas

Abstract: Purpose In RTOG 9704, as previously published, patients with resected pancreatic adenocarcinoma received continuous infusion 5-FU and concurrent radiotherapy (5FU-RT). 5FU-RT treatment was preceded and followed by randomly assigned chemotherapy, either 5-FU or gemcitabine. This analysis explored whether failure to adhere to specified RT guidelines influenced survival and/or toxicity. Methods and Materials RT requirements were protocol specified. Adherence was scored as per protocol (PP) or less than per prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
170
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(175 citation statements)
references
References 42 publications
4
170
0
1
Order By: Relevance
“…It has been shown that the quality and consistency of the trial impacts patient outcomes 1, 2, 3, 4, 5. This report identifies physics and other team member practices that specifically improve the treatment planning and delivery data for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the quality and consistency of the trial impacts patient outcomes 1, 2, 3, 4, 5. This report identifies physics and other team member practices that specifically improve the treatment planning and delivery data for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of compliance in trials and the impact on detecting changes in outcome have been demonstrated in a number of trials,1, 2, 3, 4, 6 such as TROG 02.02 on advanced head and neck cancer (Fig. 1), and in meta‐analyses of other trials.…”
Section: Introduction and Charge Of The Reportmentioning
confidence: 97%
See 1 more Smart Citation
“…This latter study did not include a review of patients who did not receive chemoradiation. Several small phase II trials have demonstrated survival of 9.6 -17 months with induction chemotherapy followed by radiation [10].…”
Section: By Jason E Farismentioning
confidence: 99%
“…We must obtain data from an optimally designed, randomized phase III trial before using an across-the-board approach with potential toxicities and implications for systemic therapy in our treatment of patients with locally advanced pancreatic cancer. analysis based on quality assurance of radiation treatment fields [10].…”
Section: By Jason E Farismentioning
confidence: 99%